A canine liver fibrosis model to develop a therapy for liver cirrhosis using cultured bone marrow–derived cells. Issue 7 (17th July 2017) - Matsuda, Takashi; Takami, Taro; Sasaki, Ryo; Nishimura, Tatsuro; Aibe, Yuki; Paredes, Bruno Diaz; Quintanilha, Luiz Fernando; Matsumoto, Toshihiko; Ishikawa, Tsuyoshi; Yamamoto, Naoki; Tani, Kenji; Terai, Shuji; et al.
Abstract : We have been developing a therapy for liver cirrhosis using cultured autologous bone marrow–derived mesenchymal stem cells (BMSCs). Before human clinical trials can be considered, the safety and efficacy of BMSC infusion in medium to large animals must be confirmed; thus, we developed a canine liver fibrosis model. A small amount of bone marrow fluid was aspirated from the canine humerus to assess the characteristics of BMSCs. We implanted a venous catheter in the stomach and a subcutaneous infusion port in the back of the neck of each canine. Repeated injection of CCl4 through the catheter was performed to induce liver cirrhosis. After 10 weeks of CCl4 injection, eight canines were equally divided into two groups: no cell infusion (control group) and autologous BMSC infusion through the peripheral vein (BMSC group). A variety of assays were carried out before and 4 weeks after the infusion. The area of liver fibrosis stained with sirius red was significantly reduced in the BMSC group 4 weeks after BMSC infusion, consistent with a significantly shortened half‐life of indocyanine green and improved liver function. Conclusion : We established a useful canine liver fibrosis model and confirmed that cultured autologous BMSC infusion improved liver fibrosis without adverse effects. ( Hepatology Communications 2017;1:691–703)